Development of asymmetric membrane capsules of metformin hydrochloride for oral osmotic controlled drug delivery - Banala, Venkatesh Teja; Srinivasan, Bharath; Rajamanickam, Deveswaran; Veerbadraiah, Basavaraj Basappa; Varadharajan, Madhavan (Asian Journal of Pharmaceutics (AJP), 2014)
Asymmetric membrane capsules are one of the novel osmotic delivery devices which offer the delivery of a wide range of drugs in a controlled manner. In the present work, we developed a semi‑automatic process by fabricating a hydraulic assisted mechanical robotic arm for the manufacturing of asymmetric membrane capsules and the process was validated in comparison with the manual procedure of manufacturing. The capsule walls were made by dip coating phase inversion process using cellulose acetate butyrate as polymer and propylene glycol as plasticizer/pore forming agent. The comparative examination of physical parameters in manual and semi‑automatic process confirmed the consistency, reproducibility and efficiency of the semi‑automatic process over manual procedure. The resulting asymmetric membrane wall was evaluated by scanning electron microscopy studies revealed the thin dense region supported on a thicker porous region. Fourier transform infrared studies showed phase inversion of the asymmetric membrane as compared to plain membrane. Osmotic release study and in vitro behavior was studied for controlled delivery of metformin hydrochloride as a model drug. In vitro release studies of the formulations showed that drug release was dependent on the concentration of pore forming agent, level of osmogents and independent of the media pH and agitation. The effect of the process variables on the drug release was optimized using 23 full factorial design and the release kinetics of the optimized formulation confirmed zero order kinetics with a controlled drug delivery of 13 h and the mechanism of drug release was found to be super case II transport.